2020
DOI: 10.1080/19476337.2020.1711813
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carrot puree with enhanced levels of chlorogenic acid on rat cognitive abilities and neural development

Abstract: 2020)Effects of carrot puree with enhanced levels of chlorogenic acid on rat cognitive abilities and neural development, ABSTRACT In this study, the effect of carrot puree with enhanced levels of chlorogenic acid, obtained from carrots treated with wounding stress, on Lactobacillus concentration in microbiota, cognitive and brain development in two generations of rats was evaluated. Wistar rats were randomly assigned three different diets: control, 90% (w/w) control + 10% carrot puree (CP), and 90% control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Previous reports have demonstrated that wounding stress application in carrots, either applied alone or in combination with UV radiation, results in the biosynthesis of antioxidant phenolic compounds [8,9]. The main phenolic compound that is accumulated is the chlorogenic acid (CHA), which has been related to the prevention and treatment of the metabolic syndrome [10], colon cancer [11,12], and the improvement in cognitive abilities and neural development [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have demonstrated that wounding stress application in carrots, either applied alone or in combination with UV radiation, results in the biosynthesis of antioxidant phenolic compounds [8,9]. The main phenolic compound that is accumulated is the chlorogenic acid (CHA), which has been related to the prevention and treatment of the metabolic syndrome [10], colon cancer [11,12], and the improvement in cognitive abilities and neural development [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, none of these bioactive properties attributed to stressed broccoli and okra have been validated with in vivo models or clinical studies. Indeed, only one report has validated the nutraceutical property of a stressed crop in vivo , where it was found that carrot puree with enhanced levels of chlorogenic acid, produced from carrots treated with wounding stress, improved rat cognitive abilities and neural development . Thus, there is a need to increase the number of in vitro and in vivo studies to understand better and validate the bioactive properties of stressed fruits and vegetables.…”
Section: Are Stressed Fruits and Vegetables Healthier? Current Knowle...mentioning
confidence: 99%
“…1 ), due to its nomenclatural divergences [45] , [46] , [47] . CGA is usually marketed as svetol, widely obtained and distributed in herbs, foods, dicotyledonous ferns and plants species namely berry fruits, tea, apple, cocoa, coffee, citrus fruits, roasted bean, pears, carrots, wormwood, artichoke, potatoes, eggplant, betel, kiwi fruits, tobacco leaves, burdock, eucommia, coffee beans, tomatoes, honeysuckle, and grapes [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] . With regards to its health boosting attributes, CGA is also significantly applied clinically, particularly against fibrosis and cancer and serves as the main constituent in traditional herbal medicine (THM) formulations for detoxification, and heat clearance [57] , [58] , [59] , [60] , [61] .…”
Section: Chlorogenic Acidmentioning
confidence: 99%